Passively Q-switched fiber laser tunable by Sagnac interferometer operation - Noor, S.F.S.M.; Zulkipli, Nur Farhanah; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2019)
In this paper, a stable passively Q-switched Erbium-doped fiber laser (EDFL) tunable by Sagnac interferometer operation was described by using a graphene oxide saturable absorber (SA) as a Q-switcher. The wavelength operation of the Q-switched EDFL was tunable from 1566.3 nm to 1559.3 nm by increasing the temperature of sagnac loop mirror (SLM) from 30 °C to 70 °C in the figure-of-eight laser configuration. At 1566.3 nm operation, by increasing the pump from the threshold power of 77.3 mW to 126.5 mW, the repetition rate can be increased from 30.7 kHz to 41.5 kHz while the pulse width was narrowed from 10.2 to 7.3 μs. The Q-switching threshold pump power increased with the increase of the temperature, which then shifted the operation to a shorter wavelength. However, the laser efficiency increased at a shorter wavelength operation. At 1561.4 nm operation, the maximum pulse energy of 20.5 nJ was obtained at 161.0 mW pump power.